Optimizing selectivity via steering dominant reaction mechanisms in steam reforming of methanol for hydrogen production - Mengyuan Zhang; Zhi Liu; Yong Yan; Diru Liu; Guangyan Xu; Yingsheng An; Yingtong Zou; Yunbo Yu; Joseph S. Francisco; Hong He (Nature Communications)
Abstract Enhancing selectivity towards specific products remains a pivotal challenge in energy catalysis. Herein, we present a strategy to refine selectivity via pathway optimization, exemplified by the rational design of catalysts for methanol steam reforming. Over traditional Pd/ZnO catalysts, the direct decomposition of key intermediates CH2O* into CO and H2 on PdZn alloys competes with the oxidation of CH2O* to CO2, leading to inferior selectivity in product distribution. To address this challenge, Cu is introduced to modify the catalytic dynamics, lowering the dissociation energy barrier of water to provide more active hydroxyl groups for the oxidation of CH2O*. Simultaneously, the CO desorption energy barrier on PdCu alloys is elevated, thereby hindering CH2O* decomposition. This dual functionality enhances both the selectivity and activity of the methanol steam reforming reaction. By modulating the activation patterns of key intermediate species, this approach provides new insights into catalyst design for improved reaction selectivity.